Atributos físicos de argissolo amarelo sob floresta e savana naturais e cultivados com pastagem em Roraima - Cruz, Diego Lima de Souza (2012)
The Roraima state shows a wide geomorphologic and soil diversity, which are results of the soil formation factor combinations. The state can be divided in three great ecosystems: the savannas, the forests and campinaranas, each one with contrasting characteristics. The livestock activity is inserted in this environmental diversity, being many times associated with the soil physics degradation. The present study was made in this context, the objective was to evaluate and compare the soil physics properties of an Yellow Argisol under savanna and forest natural areas, converted in pasture system. Representative areas of those ecosystems were selected in natural e converted order. The delineation were a randomized blocks in Split plot scheme (treatments and depth), being evaluated the following physical properties: penetration resistance (PR), soil density (SD) and particle density (PD), texture, available water capacity (AWC), moisture retention (MR), clay flocculation degree, total porosity (TP), gravimetric moisture, dispersed clay, aggregate stability, sensitivity index and soil organic matter. The texture was different between savanna and forest, being sandier on savanna, this may influenced the other attributes. The silt/clay relation was low, evidencing the high weathering state of these soils. The soil density was superior in both savanna areas, don’t showing differences between Converted Savanna (CS) and Natural Savanna (NS) in any depth. The conversion of the Natural Forest (NF) caused an increase of SD only on the superficial depth, therefore not having difference between NF and Converted Forest (CF). The average PD value was 2,66 g cm-3 that is typical of kaolinite. The PR varied in function of the areas and the depths, the greater value was observed on CS and the minor on the NF, having influence of the conversion in this attribute. The moisture values presented differences between the treatments; however, this attribute doesn’t vary with the depth in any treatment. The TP was superior on NF and inferior on CS, having TP decrease with the depths. The forest conversion doesn’t affected the aggregate size in any depths, having no harmful effects to the aggregate stability with the pasture installation, the savanna areas doesn’t show the same reaction. The AWC was only superior on the NF at 0 – 10 cm depth. The other treatments did not differ at this same depth. The MR was greater where occurred minor density and major porosity, being also related with the depth and organic matter. This attribute was superior on the forests areas, especially at NF, that differed from the CF only at the 0 – 10 cm depth. Among the savanna areas were not observed differences in any depths. It was concluded that the natural environment conversions at pasture systems caused significant changes in some physical attributes and the savanna areas were less sensitive to the changes that were caused to the pasture deployment.